Synthesis of Photodegradable Additive for Low Density Polyethylene - Santhoskumar, A.U.; Marshal, D.; Palanivelu, K.; Kumudha, T. (Asian Journal of Chemistry, 2012)
A ferrous recinoleate maleic dextrose additive was successfully synthesized and its performance on the photodegradability of low density polyethylene film was evaluated by observing the disparity in the structural characteristic, surface morphology, mechanical properties, thermal properties, optical properties, rheological properties and density measurement. Low density polyethylene films blended with 1:1 ratio of ferrous recinoleate maleic dextrose additive were prepared by melt blending. Degraded films were subjected to Fourier transformed infrared spectroscopy, scanning electron microscopy, universal testing machine to investigate its structural, morphological, mechanical properties respectively.